2021
DOI: 10.1016/j.celrep.2021.109628
|View full text |Cite
|
Sign up to set email alerts
|

Cooperativity mediated by rationally selected combinations of human monoclonal antibodies targeting the henipavirus receptor binding protein

Abstract: SUMMARY Hendra virus and Nipah virus (NiV), members of the Henipavirus (HNV) genus, are zoonotic paramyxoviruses known to cause severe disease across six mammalian orders, including humans. We isolated a panel of human monoclonal antibodies (mAbs) from the B cells of an individual with prior exposure to equine Hendra virus (HeV) vaccine, targeting distinct antigenic sites. The most potent class of cross-reactive antibodies achieves neutralization by blocking viral attachment t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 79 publications
(88 reference statements)
0
50
0
Order By: Relevance
“…The nAH1.3 mAb was previously shown to potently neutralize NiV-M, NiV-B, and HeV in vitro ( 31 ). Using a green fluorescent protein (GFP)–encoding, replication-competent Cedar (henipa)virus (rCedV) chimeras in which the native glycoproteins are substituted with the NiV-B (rCedV-NiV-B-GFP) or the HeV (rCedV-HeV-GFP) F and G glycoproteins ( 35 ), we determined nAH1.3 half-maximum inhibitory concentrations (IC 50 ) of 33 and 32 ng/ml, respectively (fig. S3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nAH1.3 mAb was previously shown to potently neutralize NiV-M, NiV-B, and HeV in vitro ( 31 ). Using a green fluorescent protein (GFP)–encoding, replication-competent Cedar (henipa)virus (rCedV) chimeras in which the native glycoproteins are substituted with the NiV-B (rCedV-NiV-B-GFP) or the HeV (rCedV-HeV-GFP) F and G glycoproteins ( 35 ), we determined nAH1.3 half-maximum inhibitory concentrations (IC 50 ) of 33 and 32 ng/ml, respectively (fig. S3A).…”
Section: Resultsmentioning
confidence: 99%
“…3B). We then carried out virus neutralization assays using rCedV-NiV-B-GFP or rCedV-HeV-GFP to examine whether these mAbs had synergistic virus-neutralizing activity ( 35 ). Using a concentration matrix of each mAb, we found that combining m102.4 and nAH1.3 led to synergistic neutralization of the two rCedV chimeras (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutralizing antibodies to NiV bind to two viral surface glycoproteins, G and F [36,38,40,41,45,46]. Recently isolated and characterized F monoclonal antibodies are prefusion specific and directed to epitopes near the apex of NiV F located within domain 3 [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Based on experience with related paramyxoviruses and pneumoviruses, both the NiV F and G proteins are considered relevant protective antigens and targets for vaccine-elicited neutralizing antibodies. Several recently isolated and characterized monoclonal antibodies have shown F-binding neutralizing antibodies to be pre-F specific (49)(50)(51)(52) and five major antigenic sites have been identified on HeV G that inhibit virus by multiple mechanisms and are cross-reactive with NiV G (53,54). The neutralizing humoral response primarily targets G, which has been the primary focus of vaccine development.…”
Section: Introductionmentioning
confidence: 99%